A 'mixed reality' simulator concept for future Medical Emergency Response Team training. Issue 4 (6th January 2017) - Stone, Robert J; Guest, R; Mahoney, P; Lamb, D; Gibson, C
Abstract : The UK Defence Medical Service's Pre-Hospital Emergency Care (PHEC) capability includes rapid-deployment Medical Emergency Response Teams (MERTs) comprising tri-service trauma consultants, paramedics and specialised nurses, all of whom are qualified to administer emergency care under extreme conditions to improve the survival prospects of combat casualties. The pre-deployment training of MERT personnel is designed to foster individual knowledge, skills and abilities in PHEC and in small team performance and cohesion in 'mission-specific' contexts. Until now, the provision of airborne pre-deployment MERT training had been dependent on either the availability of an operational aircraft (eg, the CH-47 Chinook helicopter) or access to one of only two ground-based facsimiles of the Chinook 's rear cargo/passenger cabin. Although MERT training has high priority, there will always be competition with other military taskings for access to helicopter assets (and for other platforms in other branches of the Armed Forces). This paper describes the development of an inexpensive, reconfigurable and transportable MERT training concept based on 'mixed reality' technologies—in effect the 'blending' of real-world objects of training relevance with virtual reality reconstructions of operational contexts.